Effectiveness of E-KTP Recording and Digital Population Identity Activation at the Population and Civil Registration Service of Minahasa Regency, North Sulawesi Province (International Forum of Researchers and Lecturers, 2025)
The background of this study is that the high number of KTP recordings is not commensurate with the still low activation of Digital Population Identity (IKD) in Minahasa Regency, North Sulawesi Province. The low activation rate indicates the need to analyze the effectiveness of efforts that have been made by related agencies. This study aims to analyze how effective the Population and Civil Registration Service (Disdukcapil) is in increasing the recording of Resident Identity Cards and activation of Digital Population Identity in Minahasa Regency, the obstacles experienced and efforts made to increase IKD activation in Minahasa Regency. The research method used is a qualitative descriptive method. Data collection techniques include interviews, observation, and documentation. The theory used in this study is the concept of organizational effectiveness according to Duncan in Steers (1985), which includes the dimensions of goal achievement, integration, and adaptation. The results of this study indicate that the effectiveness of the Population and Civil Registration Service in increasing KTP recording and Digital Population Identity Activation in Minahasa Regency is not optimal. In the dimension of goal achievement, IKD activation has not reached the target of 30% of the population required to have a KTP. In the dimension of integration, IKD has not been integrated due to the lack of cooperation with other agencies. Meanwhile, in the dimension of adaptation, the improvement of IKD operator capabilities has been good in providing IKD activation services, but in terms of facilities and infrastructure it is still inadequate.